Distribution of organochlorines and ecological risks in surface sediments from El-Mex Bay, Mediterranean Sea. Issue 7 (3rd October 2017) - Said, Tarek O.; El Zokm, Gehan M.; Mohamed, Laila A.; Okbah, Mohamed A.; Soliman, Naglaa F.
ABSTRACT: Polychlorinated biphenyls (PCBs) and organochlorine pesticides (OCPs) were determined in eight sampling sites collected from El-Mex Bay sediments during the period of 2013–2015. Concentrations of PCBs, Hexachlorocyclohexanes (HCHs), Dichloro Diphenyl Trichloroethanes (DDTs), and cyclodienes ranged from 0.148 to 23.99, ND to 0.089, ND to 4.64, and 0.005 to 0.581 ng g −1 dry wt, respectively. Total organic carbon (TOC) was relatively low, ranging from 0.09% to 1.42%. Total carbonate content ranged from 38% to 58%. The negative correlation of TOC with total pesticides (r = −0.18) suggested that TOC does not have a role binding with pesticides. On the other hand, a positive correlation between PCBs and TOC (r = 0.254 at p > 0.01) was observed probably due to the low solubility of PCBs in the seawater. So, it will continue to precipitate until it reaches the bottom water and contaminates the sediment. The data obtained in the present work compared well with the counterpart data reported internationally. In general, the results of PCBs and OCP concentrations in El-Mex Bay sediments were much lower than the permissible levels recorded by sediment quality guidelines (SQGs). Interestingly, the organochlorines in sediments of El-Mex Bay were below the respective SQG values and were not likely to pose potential biological adverse impact.